Increased frequency of chromosome translocations in airline pilots with long-term flying experience. Issue 1 (11th December 2008) - Yong, L C; Sigurdson, A J; Ward, E M; Waters, M A; Whelan, E A; Petersen, M R; Bhatti, P; Ramsey, M J; Ron, E; Tucker, J D
Abstract : Background: Chromosome translocations are an established biomarker of cumulative exposure to external ionising radiation. Airline pilots are exposed to cosmic ionising radiation, but few flight crew studies have examined translocations in relation to flight experience. Methods: We determined the frequency of translocations in the peripheral blood lymphocytes of 83 airline pilots and 50 comparison subjects (mean age 47 and 46 years, respectively). Translocations were scored in an average of 1039 cell equivalents (CE) per subject using fluorescence in situ hybridisation (FISH) whole chromosome painting and expressed per 100 CE. Negative binomial regression models were used to assess the relationship between translocation frequency and exposure status and flight years, adjusting for age, diagnostic x ray procedures, and military flying. Results: There was no significant difference in the adjusted mean translocation frequency of pilots and comparison subjects (0.37 (SE 0.04) vs 0.38 (SE 0.06) translocations/100 CE, respectively). However, among pilots, the adjusted translocation frequency was significantly associated with flight years (p = 0.01) with rate ratios of 1.06 (95% CI 1.01 to 1.11) and 1.81 (95% CI 1.16 to 2.82) for a 1- and 10-year incremental increase in flight years, respectively. The adjusted rate ratio for pilots in the highest compared to the lowest quartile of flight years was 2.59 (95% CI 1.26 to 5.33). Conclusions: Our data suggests that pilots with long-term flying experience may be exposed to biologically significant doses of ionising radiation. Epidemiological studies with longer follow-up of larger cohorts of pilots with a wide range of radiation exposure levels are needed to clarify the relationship between cosmic radiation exposure and cancer risk.